2002
DOI: 10.1046/j.1365-2745.2002.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulp handling by vertebrate seed dispersers increases palm seed predation by bruchid beetles in the northern Amazon

Abstract: 1The simultaneous use of fruits and seeds by invertebrate seed predators and vertebrate seed dispersers produces complex ecological interactions that reduce the predictability of seed fate. 2 Cocosoid palm seeds in the Neotropics are subject to high mortality by bruchid beetle infestation and such attack is the major cause of mortality for seeds of the palm Attalea maripa at our study site in the northern Brazilian Amazon. 3 The exocarp and mesocarp of 1400 fruits were manipulated in different ways to simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 61 publications
(89 reference statements)
2
66
1
8
Order By: Relevance
“…All palm bruchids (subfamily Pachymerinae) were believed to be in guild C, infesting endocarps only after fruit have fallen to the ground (Johnson & Romero 2004). Removal of the exocarp and mesocarp facilitates subsequent oviposition and enhances seed predation by guild C species, for example in Speciomerus giganteus attacking Attalea butyracea in Costa Rica and Panama (Janzen 1971b, Wright 1983, in P. cardo attacking A. maripa in Brazil (Silvius & Fragoso 2002), and in Caryoborus serripes attacking Astrocaryum chambira in Peru (Delgado et al 1997). Exocarps protect seeds against guild C species, and fruit handling by mammals gives bruchid beetles access to the endocarps (Silvius 2005).…”
Section: Bruchid Versus Scolytid Beetlesmentioning
confidence: 99%
“…All palm bruchids (subfamily Pachymerinae) were believed to be in guild C, infesting endocarps only after fruit have fallen to the ground (Johnson & Romero 2004). Removal of the exocarp and mesocarp facilitates subsequent oviposition and enhances seed predation by guild C species, for example in Speciomerus giganteus attacking Attalea butyracea in Costa Rica and Panama (Janzen 1971b, Wright 1983, in P. cardo attacking A. maripa in Brazil (Silvius & Fragoso 2002), and in Caryoborus serripes attacking Astrocaryum chambira in Peru (Delgado et al 1997). Exocarps protect seeds against guild C species, and fruit handling by mammals gives bruchid beetles access to the endocarps (Silvius 2005).…”
Section: Bruchid Versus Scolytid Beetlesmentioning
confidence: 99%
“…As such, it is possible that there is, in fact, seasonal variation in predation as was reported by Silvius & Fragoso (2002), who observed the predation rate of P. cardo on A. maripa to vary from 60 to 94 %, during the dry and rainy seasons, respectively. Attalea phalerata fruits exposed for eight months, including the rainy season, demonstrated 60 % predation by P. cardo (Castro & Roldan 2001), although A. arenaria, which also demonstrated continuous fruiting, suffered 20.6 % predation by P. nucleurum (Grenha et al 2008).…”
Section: Discussionmentioning
confidence: 81%
“…Acrocomia aculleata, A. speciosa, and Syagrus oleracea, which grow up to 10 m in height, likewise demonstrated seed predation by P. nucleurum (a congeneric species) only in the post-dispersal phase (Garcia et al 1980;Scariot 1998). However, Silvius & Fragoso (2002) and Grenha et al (2008) reported seed predation in the shorter palms (approximately 2 m tall) Bactris acanthocarpa and Allagoptera arenaria (Arecaceae) (Dasyprocta spp. ; Dasyproctidae) (Guix 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations